Colocalization of genetic regions that confer resistance/susceptibility against Puccinia species and association with Pyrenophora teres loci within the barley genome - Clare, Shaun J.; Novakazi, Fluturë; Hayes, Patrick M.; Moscou, Matthew J.; Brueggeman, Robert S. (Frontiers in Agronomy, 2024)
Cereal rust diseases, including leaf, stem, and stripe rust, are some of the most devastating and economically important diseases of barley. However, host–pathogen genetic interaction research for each pathosystem is typically conducted independently and in isolation. Examples of host resistance/susceptibility genes functioning sympathetically to multiple pathogens or antagonistically to additional pathogens have been reported. Therefore, consolidation of loci that have been reported in multiple studies and across pathosystems is useful for variety development to maximize resistance to multiple pathogens and avoid inadvertent incorporation of susceptibility loci that act antagonistically to other pathogens. This review summarizes loci reported in three key biotrophic pathosystems of barley, including leaf, stem, and stripe rust. In conjunction with previously consolidated net blotch loci, this review lays the foundation for a wider barley rust resistance/susceptibility atlas. This review aims to inform breeders and researchers in rapidly identifying accessions and loci that need further characterization and which loci would be most useful to introgress into elite varieties.